US-Afghanistan War and its Ramifications - FETHIZA ALI, HAMATI, Aicha Dounia (University of El-oued, 2022)
The war on terror is the recent greatest and longest war of all times. The current study attempts to investigate the most prominent war between the US and Afghanistan that began on 11th, September 2001 to 2021. It highlights the different ramifications and implications of the US-Afghanistan conflict. In order to conduct this study,three questions have been asked. The first inquired on the reasons behind which the US invaded Afghanistan. The second examined the withdrawal strategies along with the ways of ending the war. The third scrutinized the ramifications of US-Afghanistan war. To respond to the questions three hypotheses have been formulated. The first sought to highlight the relationship between the invasion of Afghanistan and quelling the terrorism in its territory. The Second hypothesized that the US intention of ending the can be traced through series of withdrawal policies.The third related to the effects of ending the war which led several ramifications that affect international relations. In order to investigate the validity of our hypotheses, we selected the corpora subject to this study from literature available, using the techniques of the historical and descriptive- methods. Accordingly, the study revealed the following results; Us-Afghanistan war caused serious ramifications on all levels: economically, socially and psychologically on both countries. الحرب على الإرهاب هي أحدث وأطول حرب في كل العصور. تحاول الدراسة الحالية التحقيق في أبرز حرب بين الولايات المتحدة وأفغانستان والتي بدأت في 11 سبتمبر 2001 إلى 2021. وهي تسلط الضوء على تداعيات وانعكاسات مختلفة للصراع بين الولايات المتحدة وأفغانستان. من أجل إجراء هذه الدراسة ، تم طرح ثلاثة أسئلة. استفسر الأول عن أسباب غزو الولايات المتحدة لأفغانستان. أما الثاني فقد تناول استراتيجيات الانسحاب وطرق إنهاء الحرب. وفحص الثالث تداعيات الحرب بين الولايات المتحدة وأفغانستان. للرد على الأسئلة تمت صياغة ثلاث فرضيات. الأول سعى إلى إبراز العلاقة بين غزو أفغانستان وقمع الإرهاب في أراضيها. افترضت الفرضية الثانية أن نية الولايات المتحدة بإنهاء يمكن تتبعها من خلال سلسلة من سياسات الانسحاب. والثالث يتعلق بآثار انتهاء الحرب التي أدت إلى تداعيات عديدة أثرت على العلاقات الدولية. من أجل التحقق من صحة فرضياتنا ، اخترنا المجسم الخاضع لهذه الدراسة من الأدبيات المتاحة ، باستخدام تقنيات الأساليب التاريخية والوصفية. وعليه توصلت الدراسة إلى النتائج التالية: تسببت الحرب الأمريكية الأفغانية في تداعيات خطيرة على جميع المستويات: اقتصاديًا واجتماعيًا ونفسيًا في كلا البلدين.
Keywords: Conflict, Ramifications, US-Afghanistan War .; الصراع، الانفراج، الحرب الأمريكية الأفغانية.